RUANG BARISAN KONVERGEN LACUNARY STATISTIK - Haryadi - Haryadi; Solikhin - Solikhin (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2023)
In this paper, we use the concept of lacunary statistic convergence to construct a linear metric space and then examine its topological properties. We show that the space includes the space of bounded sequence and the space of strong summable Cesaro of order one. Furthermore, the linear metric space is an FK-space but has not AK property.